2020
DOI: 10.1101/2020.09.02.280198
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SUMOylation- and GAR1-dependent regulation of dyskerin nuclear and subnuclear localization

Abstract: SummaryDyskerin, a telomerase-associated protein and H/ACA ribonucleoprotein complex component plays an essential role in human telomerase assembly and activity. The nuclear and subnuclear compartmentalization of dyskerin and the H/ACA complex is an important though incompletely understood aspect of H/ACA ribonucleoprotein function. The posttranslational modification, SUMOylation, targets a wide variety of proteins, including numerous RNA-binding proteins, and most identified targets reported to date localize … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 90 publications
(100 reference statements)
0
4
0
Order By: Relevance
“…In support of this idea, SUMOylation of the snoRNP component NOP58 was shown to facilitate its interaction with Box C/D snoRNA, thereby targeting snoRNPs to the nucleolus (Westman et al, 2010). Similarly, miscibility of Dyskerin (DKC1) within the nucleolar DFC was proposed to rely on SUMO-dependent binding of DKC1 to a SIM in GAR1, a component of the H/ACA snoRNP complex (MacNeil et al, 2021). Altogether, these data suggest that SUMO may contribute to phase separation in the nucleolar compartment.…”
Section: Sumo Conjugation-deconjugation In the Nucleolusmentioning
confidence: 93%
“…In support of this idea, SUMOylation of the snoRNP component NOP58 was shown to facilitate its interaction with Box C/D snoRNA, thereby targeting snoRNPs to the nucleolus (Westman et al, 2010). Similarly, miscibility of Dyskerin (DKC1) within the nucleolar DFC was proposed to rely on SUMO-dependent binding of DKC1 to a SIM in GAR1, a component of the H/ACA snoRNP complex (MacNeil et al, 2021). Altogether, these data suggest that SUMO may contribute to phase separation in the nucleolar compartment.…”
Section: Sumo Conjugation-deconjugation In the Nucleolusmentioning
confidence: 93%
“…FLAG co-IP of FLAG-NLS-hTERT truncations coupled to quantitative real-time polymerase chain reaction (qPCR) of hTR was performed as previously described ( 46 ). Briefly, transfected HEK293 cells were washed with ice-cold PBS 1× and then suspended in 150 μl low-salt cytosolic lysis buffer (25 mM Hepes pH 7.9, 0.5 mM MgCl 2 , 5 mM KCl, 0.5% NP-40 + 1× protease inhibitor + 0.04 U/μl RNaseOUT (Life Technologies)).…”
Section: Methodsmentioning
confidence: 99%
“…SUMOylation sites were identified in dyskerin (Hendriks and Vertegaal 2016;Becker et al 2013;Hendriks et al 2014;Lamoliatte et al 2017;Hendriks et al 2018), of which several are located in its lysine-rich C-terminal NLS. Dyskerin lacking the C-terminal residues 446-514 accumulates mostly in the cytoplasm (MacNeil et al 2021). The fusion of this cytoplasmic localized truncation variant with SUMO3 restores nuclear accumulation, but not nucleolar localization, possibly due to the loss of NoLS in this C-terminal region along with important residues that might regulate the nucleolar localization of dyskerin, such as K467.…”
Section: H/aca Rnp Biogenesis and Cellular Localizationmentioning
confidence: 99%
“…These studies also identified a short non-covalent SUMO-interaction motif in GAR1. Thus, SUMO plays an important role in the H/ACA RNP biogenesis and its localization to the nucleolus (MacNeil et al 2021). In addition to SUMO, the single-strand-selective monofunctional uracil DNA glycosylase 1 (SMUG1) is involved in the localization of dyskerin.…”
Section: H/aca Rnp Biogenesis and Cellular Localizationmentioning
confidence: 99%